THE EFFECT OF THE USE OF GALLERY WALK LEARNING METHODS ON STUDENT LEARNING OUTCOMES IN SMP NEGERI 1 ENDE - Reni Maria Jimun; Ilyas Ilyas; Adrianus Nasar (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
This study aims to determine the effect of the use of the gallery walk method of learning outcomes of VII grade students of SMP Negeri 1 Ende in the 2019/2020 Academic Year. This type of research is survey research with an ex-post facto research design. The population in this study were students of class VII A, B, C of SMP Negeri 1 Ende, with a sample of 51 students who were obtained using a simple random sampling technique. Data obtained through interviews and documentation, in the form of student learning outcomes data. Data analysis was used by t-test. The results showed that learning activities using the gallery learning method go students learning outcomes, which obtained the value of t =14.531, with =12.510. the value of sig. (2-tailed) 0,000 < 0,05 with α = 0,05.